(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Empowerment has been a common buzzword among activists and academics, as well as among legislators, health care providers, and educators, social workers, and managers, not to mention disadvantaged communities, a community, state, or nation cannot function effectively without the participation and empowerment of women. In a child’s early years, a woman has the most influence. Women play a crucial role in our culture. Education as a tool for women’s empowerment might result in a shift in attitudes. Hence, it is critical for India’s socio-economic and political development. And the study which disused about social issues, Economic issues, Political issues, Political participation